Temperament and personality: the German version of the Adult Temperament Questionnaire (ATQ) - Wiltink, Jörg (German Medical Science GMS Publishing House, 2006)
The psychobiological orientation inherent in temperament concepts permits a close tie between temperament and the rapidly proliferating research areas of neurosciences and behavioural genetics. Based on developmental and psychobiological studies, the Adult Temperament Questionnaire (ATQ) by Rothbart measures self-regulatory processes in addition to constitutionally based individual reactivity. The purpose of this paper is to validate a German version of the short form of the ATQ with 77 items. 213 psychosomatic inpatients and outpatients and 116 control subjects took part in this study. The study included standardized measures of personality and symptoms. The German version reliably measures the four dimensions negative affect, extraversion, orienting sensitivity and effortful control; subscales were moderately correlated. We found a consistent pattern of correlation to personality (NEO-FFI) and interpersonal problems (IIP), negative affect strongly correlated with neuroticism; effortful control correlated with conscientiousness, orienting sensitivity with openness, and extraversion correlated with the corresponding scale of the NEO-FFI. According to our hypothesis, negative affect was positively correlated with higher distress and physical complaints, while effortful control was negatively correlated with them. When negative affect and effortful control were combined, effortful control had a moderating effect on distress. Clinical and non-clinical samples differed significantly on all dimensions; the ATQ appears to be suitable for differentiating subgroups of patients according to self-regulation.